Poly-ADP Ribosyl Polymerase 1 (PARP1) Regulates Influenza A Virus Polymerase - Liset Westera; Alisha M. Jennings; Jad Maamary; Martin Schwemmle; Adolfo García-Sastre; Eric Bortz (Advances in Virology)
Influenza A viruses (IAV) are evolutionarily successful pathogens, capable of infecting a number of avian and mammalian species and responsible for pandemic and seasonal epidemic disease in humans. To infect new species, IAV typically must overcome a number of species barriers to entry, replication, and egress, even while virus replication is counteracted by antiviral host factors and innate immune mechanisms. A number of host factors have been found to regulate the replication of IAV by interacting with the viral RNA-dependent RNA polymerase (RdRP). The host factor PARP1, a poly-ADP ribosyl polymerase, was required for optimal functions of human, swine, and avian influenza RdRP in human 293T cells. In IAV infection, PARP1 was required for efficient synthesis of viral nucleoprotein (NP) in human lung A549 cells. Intriguingly, pharmacological inhibition of PARP1 enzymatic activity (PARylation) by 4-amino-1,8-naphthalimide led to a 4-fold increase in RdRP activity, and a 2.3-fold increase in virus titer. Exogenous expression of the natural PARylation inhibitor PARG also enhanced RdRP activity. These data suggest a virus-host interaction dynamic where PARP1 protein itself is required, but cellular PARylation has a distinct suppressive modality, on influenza A viral polymerase activity in human cells.